Interactive web-based pulmonary rehabilitation programme: a randomised controlled feasibility trial. Issue 3 (31st March 2017) - Chaplin, Emma; Hewitt, Stacey; Apps, Lindsay; Bankart, John; Pulikottil-Jacob, Ruth; Boyce, Sally; Morgan, Mike; Williams, Johanna; Singh, Sally
Abstract : Objectives: The aim of this study was to determine if an interactive web-based pulmonary rehabilitation (PR) programme is a feasible alternative to conventional PR. Design: Randomised controlled feasibility trial. Setting: Participants with a diagnosis of chronic obstructive pulmonary disease were recruited from PR assessments, primary care and community rehabilitation programmes. Patients randomised to conventional rehabilitation started the programme according to the standard care at their referred site on the next available date. Participants: 103 patients were recruited to the study and randomised: 52 to conventional rehabilitation (mean (±SD) age 66 (±8) years, Medical Research Council (MRC) 3 (IQR2–4)); 51 to the web arm (mean (±SD) age 66 (±10) years, MRC 3 (IQR2–4)). Participants had to be willing to participate in either arm of the trial, have internet access and be web literate. Interventions: Patients randomised to the web-based programme worked through the website, exercising and recording their progress as well as reading educational material. Conventional PR consisted of twice weekly, 2 hourly sessions (an hour for exercise training and an hour for education). Outcome measures: Recruitment rates, eligibility, patient preference and dropout and completion rates for both programmes were collected. Standard outcomes for a PR assessment including measures of exercise capacity and quality of life questionnaires were also evaluated. Results: A statistically significant improvement (p≤0.01) was observed within each group in the endurance shuttle walk test (WEB: mean change 189±211.1; PR classes: mean change 184.5±247.4 s) and Chronic Respiratory disease Questionnaire-Dyspnoea (CRQ-D; WEB: mean change 0.7±1.2; PR classes: mean change 0.8±1.0). However, there were no significant differences between the groups in any outcome. Dropout rates were higher in the web-based programme (57% vs 23%). Conclusions: An interactive web-based PR programme is feasible and acceptable when compared with conventional PR. Future trials maybe around choice-based PR programmes for select patients enabling stratification of patient care. Trial registration number: ISRCTN03142263 ; Results.